Implicit and explicit “European clauses” in the Italian Constitution - Lupo, Nicola (Toruńskie Studia Polsko-Włoskie, 2022)
The contribution analyzes the links between the Italian Constitution and the process of European integration, which are generally outlined by what are called “European clauses”: the constitutional provisions – contained in the original text of the Constitution of the Member States or introduced later – which, with very varied formulas, allow or require the accession to the European Union, possibly setting limits and conditions to future stages of the process of European integration. To this end, a large part of the contribution is devoted to the analysis of the provision that has functioned as an “implicit and general” European clause: namely, article 11 of the Italian Constitution. The contribution retraces its origins, in the Constituent Assembly and in the light of the fascist experience, its multiple (but closely) connected contents and, above all, the interpretation of this article that has been affirmed, since the 1950s, in order to implement in Italy the Treaties establishing the European Communities. It also takes into account the consultative referendum held in 1989 and the constitutional revisions approved subsequently, which introduced specific and explicit references to the European Union (the most important of which in articles 81, 97, 117 and 119 of the Constitution), albeit without ever replacing the general clause in article 11 and its crucial role. It is argued that the use of article 11 of the Constitution as an „implicit and general European clause”, although originally due to peculiar historical and political circumstances, has represented a crucial and now foundational junction in the evolution of the Italian Constitution. The openness to international organizations aimed at promoting peace and justice among nations and the necessity of the consequent limitations of sovereignty have allowed Italy to figure among the promoters of the various phases of European integration; and the Republican Constitution to evolve, over more than seventy years, in full coherence with its founding values, for the most part without the need to resort to constitutional revisions.